Dying in the ICU: changes in end of life decisions from 2011 to 2018 in the ICU of a communal tertiary hospital in Germany - Schulmeyer, Isabel; Weigand, Markus A.; Heinzel-Gutenbrunner, Monika; Gruß, Marco (Die Anaesthesiologie, 2022)
With modern intensive care medicine, even older patients and those with pre-existing conditions can survive critical illnesses and major operations; however, unreflected application of intensive care treatment might lead to a state called chronic critical illness. Today, withholding treatment and/or treatment withdrawal precede many deaths in the intensice care unit (ICU). We looked at changes in measures at the end of life and withholding or withdrawal of treatment in the ICU of a German tertiary hospital in 2017/2018 compared to 2011/2012.